Z1456467176 alleviates gouty arthritis by allosterically modulating P2X7R to inhibit NLRP3 inflammasome activation - Li, Xiaoling; Liu, Yiming; Luo, Chengyu; Tao, Jinhui (Frontiers in Pharmacology, 2022)
NLRP3 inflammasome activation is a central process in initiating gout flares. The unique conformational rearrangement of the P2X7 receptor (P2X7R) upon ATP binding is critical for the activation of the NLRP3 inflammasome. However, studies on allosteric modulation of P2X7R in gout treatment are limited. Here, we aimed to investigate the therapeutic implications of targeting P2X7R in gout by designing a P2X7R allosteric inhibitor and validating the inhibitory function on NLRP3 inflammasome activation. Through virtual screening, we identified Z1456467176 (N-3-[(2-aminoethyl)sulfamoyl]phenyl-2-methyl-3-[3-(trifluoromethyl)phenyl] propanamide hydrochloride) bound to the drug-binding pocket as a potential antagonist of P2X7R. In functional assays, ATP- or BzATP-induced P2X7R function was assessed in vitro in HEK-293T cells overexpressing hP2X7R (dye uptake assay) and macrophages (IL-1β release assay). Z1456467176 exhibited a stable and significant P2X7R inhibitory effect. Importantly, in MSU crystal-induced gout, the presence and involvement of ATP were confirmed. Z1456467176 blocked ATP-induced activation of the NLRP3-caspase-1-IL-1β pathway and exerted promising effects in reducing gouty joint inflammation in rats. In addition, molecular docking and molecular dynamics simulation studies showed that the P27XR protein conformation was remodeled by Z1456467176 binding. Collectively, our results provide a potent P2X7R allosteric inhibitor that facilitates the remission of MSU crystal-induced gout inflammation by inhibiting NLRP3 inflammasome activation, suggesting that allosteric inhibition of P2X7R represents a new direction in gout treatment.